Palliative repeated electroporations of oral tumours in dogs: A case series - Moretti, Giulia; Dentini, Alfredo; Beccati, Francesca; Arcelli, Rolando; Matteo, Irene Di; Giovannini, Giuseppe; Bufalari, Antonello (Frontiers in Veterinary Science, 2022)
Electrochemotherapy (ECT) is a highly developed treatment for many solid tumours that provides good local control in 80% of neoplasms in dogs. ECT can be used to treat different types of tumours, particularly as an innovative approach for non-resectable masses. As reported in the literature, electroporation-based treatments are safe, simple, fast and cost-effective treatment alternatives for selected oral and maxillofacial tumours not involving the bone in dogs (e.g., small squamous cell carcinoma or malignant melanoma). In this descriptive retrospective paper, the authors describe the outcome of various types of oral tumours treated with ECT as a palliative first line treatment or as a rescue treatment in dogs with local tumour recurrence. Nineteen dogs were included and treated with at least one session of three electroporations coupled with intravenous administration of bleomycin every 21 days. Tumour size, localization, histotype, stage, recurrence, solid tumour response evaluation criteria (RECIST), local toxicity, progression free survival (PFS) and median survival time (MST) were evaluated. The small population did not allow the analysis of the ECT response by comparing different tumour types; further studies with a larger caseload are needed. However, all dogs, despite the low MST, showed a good local response to treatment with a rapid improvement in quality of life from the first ECT application; no side effects attributable to chemotherapy have been detected and toxicity due to the electroporation was minimal and well tolerated in all dogs.